Length/weight relationship of pink shrimps Farfantepenaeus brasiliensis and Farfantepenaeus paulensis, off Rio de Janeiro State, Brazil - de Andrade-Tubino, Magda Fernandes; Ostrovski, Maria Cristina (Arquivos de Ciências do Mar, 2017)
During the period July/2000 – February/2001 individuals of Farfantepenaeus brasiliensis and F. paulensis, caught in Cabo Frio area (Rio de Janeiro – Brazil) were sampled for biometric studies. The material amounted to 255 specimens F. brasiliensis and 166 specimens of F. paulensis. For each shrimp the carapace length and the total weight were measured. For F. brasiliensis the length/weight relationship showed no statistically-significant differences between males and females, being expressed by the equations: loge W = -9.879 + 3.324 loge L (r = 0.924; P < 0.01) and W = 0.0000512 . L 3.324. For F. paulensis, this relationship was statistically sex-differentiated, as expressed by equations – males: loge W = - 9.275 + 3.173 loge L (r = 0.948; P < 0.01) and W = 0.000092 . L3.173 ; females: loge W = - 7.820 + 2.811 loge L (r = 0.969; P < 0.01) and W = 0.000402. L2.811. Since only F. paulensis showed sexual dimorphism in the length/ weight relationship, it is deemed necessary to obtain a new estimate of the regression parameters because the scientific literature indicates biometric differences between males and females for all species of genus Farfantepenaeus (Bukurovsky).